ELAZIĞ İLİNDE GÖREV YAPAN SAĞLIK ÇALIŞANLARININ ÇOCUK İHMALİ VE İSTİSMARI KONUSUNDA FARKINDALIK DÜZEYLERİ VE BU DURUMU ETKİLEYEN FAKTÖRLER - UNCU, FATOŞ (Fırat Üniveristesi, 2013)
Çocuk ihmali ve istismarı; tüm toplumlarda sık görülen ve yaşamda kalıcı olumsuz izler bırakabilen önemli halk sağlığı sorunlarından biridir. Bu araştırma Elazığ il merkezinde görev yapan sağlık çalışanlarının çocuk ihmali ve istismarı konusunda farkındalık düzeylerini ve bu durumu etkileyen faktörleri saptamak amacıyla gerçekleştirildi.Elazığ ilinde görev yapan sağlık çalışanları araştırmanın evrenini oluşturmuş, n=Nt²pq/d²(N-1)t²pq formülünden yararlanılarak (t=2.59,d=0.03, p=0.30), örnekleme 906 kişi seçildi ve 899 kişiye (%99.2) ulaşıldı. Çalışma verileri genelde çoktan seçmeli sorulardan oluşan bir anket formu ve "Çocuk İstismarı ve İhmalinin Belirti ve Risklerinin Tanılanmasına Yönelik Ölçek Formu" ile toplandı.Araştırma kapsamına alınan sağlık çalışanlarından %46.4'ü hekim, %53.6'sı hemşire ve ebedir. Sağlık çalışanlarının yaş ortalaması 33.6±7.7'dir ve %61.6'sı kadındır. Hekimlerin (3.67±0.29) çocuk istismarı ve ihmalinin belirti ve riskleri tanılama genel ölçek puanları hemşire ve ebelere (3.55±0.30) göre anlamlı düzeyde yüksek bulundu (p=0.001).Çocuk istismarı ve ihmalinin belirti ve riskleri tanılama ölçeği alt grupları puan ortalamaları hekim grubunda hemşire ve ebelere göre istatistiksel olarak anlamlı olduğu görüldü. Hekimler (3.83±0.53) ve hemşire ve ebeler (3.74±0.65) çocuk istismarı ve ihmalinin belirti ve riskleri tanılama alt ölçek gruplarından en yüksek puan ortalamasını ?çocuk üzerindeki ihmal belirtileri? alt ölçeğinden aldılar. Hekimlerin (3.41±0.49) ve hemşire ve ebelerin (3.21±0.50) çocuk istismarı ve ihmalinin belirti ve riskleri tanılama alt ölçek gruplarından en düşük puan ortalaması ?istismar ve ihmale yatkın çocuk özellikleri?dir.Sonuç olarak; Elazığ ilinde görev yapan sağlık çalışanlarının çocuk ihmali ve istismarına ilişkin farkındalık düzeyleri incelenmiş ve sağlık çalışanlarının bu konuda bilgi gereksinimlerinin olduğu belirlenmiştir.Anahtar Kelimeler: Çocuk, Hekim, Hemşire,Ebe, İhmal, İstismar

Child abuse and neglect is one of the major health problems seen in all societies that can have a permanent negative impact on one's life. This research is made to determine the awereness of the health care professionals about child abuse and neglect who work in the Elazig city center as well as the factors that affect this situation.The subjects of this study consists of the health care professionals who work in Elazığ and with the formula n=Nt²pq/d²(N-1)t²pq 906 people were selected (t=2.59,d=0.03, p=0.30) and 899(%99.2) of these people were reached. Data for the study was collected with the help of a questionnaire consisting of multiple-choice questions in general and ?Scale for Identifying Signs and Risks of Child Abuse and Neglect? .46.4% of health care workers included in the study were physicians and 53.6% were nurses and midwives. Age average of the health care workers were 33.6 ± 7.7 and 61.6% of them were female. The total scale points for identifying signs and risks of child abuse and neglect for physicians (3.67±0.29) was found to be significantly higher than those recorded for nurse and midwives (3.55±0.30) (p=0001).The average score for the sub-groups of physicians of " Scale For Identifying Signs And Risks Of Child Abuse And Neglect" were found to be statistically meaningful compared to the nurses and midwives. Both physicians (3.83±0.53) and nurses and midwives (3.74±0.65) scored highest in the subgroup "Neglect indications upon chid" of the "Identification of child abuse and neglect indications and risks" scale group. Physicians (3.41±0.49) and nurses and midwives (3.21±0.50) scored the lowest in the subgroup "Properties of a child prone to abuse and neglect" of the "Identification of child abuse and neglect indications and risks" scale group.As a result, health care workers who work in Elazig were inspected in terms of their level of their child abuse and neglect awareness and it's been determined that the health care staff needs to be informed about this subject.Key Words: Child, Physician, Nurse, Midwife, Neglect, Abuse.
Health care workers who work in the province of Elazig levels of awareness about child abuse and neglect, and the factors affecting this situation
Keywords: Hemşirelik; Halk Sağlığı